Convenient Approach to Bicyclic Sultams - Filimonchuk, Sergiy L.; Nazarenko, Kostiantyn; Shvydenko, Tetiana; Shvydenko, Kostiantyn; Rusanov, Eduard B.; Kostyuk, Aleksandr (Synthesis, 2022)
A method for the synthesis of aminomethyl-substituted five-membered sultams has been developed. The aminomethyl sultams were synthesized from the corresponding iodomethyl derivatives by nucleophilic substitution of the iodine atom with sodium azide followed by reduction on Pd/C. This method was further expanded to side-chain-substituted sultams, starting from amino acid esters, to obtain aminomethyl-containing bicycles. The simple practical procedure and available starting amino acid esters, including chiral examples, make various bicyclic sultams readily available.
Keywords: sulfonamides; bicyclic compounds; cyclization; reduction; diastereoselectivity